Prospective study of managing long bone fracture nonunion: is bone graft needed in every case? - Balagani, Srinivas (International Journal of Research in Orthopaedics, 2018)
Background: Increased road traffic accidents lead to increased incidence of fracture of long bones. It has a tendency of non-union. Infection is very common in these cases which are an important cause of nonunion of long bone fractures. The objective of the study was to study the incidence and patterns of non-union of long bone fracture. Methods: Hospital based prospective study was carried out at Department of Orthopedics, from June 2017 to March 2018. Patients admitted to wards of Department of Orthopedics with nonunion of long bones were included. During the study period a total of 20 cases were eligible for the present study as per the inclusion and exclusion criteria. Results: Males were more affected than females. Most commonly affected age group was 41-50 years and 61-70 years (25% each). Most commonly affected long bone was femur in 35% of the cases. Most common type of non-union was hypertrophic (50%). Most common cause of non-union was broken implant in 35% of the cases. Maximum number of patients had union in 4-6 months in 60% of the cases after surgery of previous non-union of long bones. Only four patients developed complications like shortening of the limb or persistent non-union. Conclusions: Hypertrophic non unions doesn’t require bone graft, they require only stable fixation. For removal of broken implant in hypertrophic non-union if we open the fracture site, then even the gap after debridement of fracture site shows partial segmental defect it doesn’t require bone grafting.